2021 February Texas Ice Storm Induced Spring GPP Reduction Compensated by the Higher Precipitation. Issue 1 (9th January 2023) - Yang, Linqing; Liu, Meng
Abstract: Climate extremes are more frequent and affect the carbon cycle. On 10–20 February, an exceptional winter storm in Texas brought severe ecological and economic effects. However, its impacts on vegetation activities and the carbon cycle are unclear. This study evaluated the early 2021 ice storm effects on spring phenology and the carbon cycle. The results showed that the ice storm led to a significant later vegetation spring phenology and a reduction of 42.32 Tg C in gross primary production (GPP) and a reduction of 34. 47 Tg C net ecosystem production (NEP) in spring. In the 2021 spring, Texas became a carbon source from the carbon sink. More precipitation in late spring and summer precipitation recharged the rootzone soil moisture, which enhanced summer vegetation GPP and NEP and compensated for the effects of the ice storm on spring carbon uptake. The summer GPP enhancement offset all the spring GPP reduction, and thus GPP was increased by 4.97% during 2021. 91.47% of the spring NEP reduction was compensated by summer NEP enhancement due to higher root zone soil moisture. Due to the NEP enhancement during autumn, NEP did not decrease as well and increased by 10.88% during 2021. This observation‐based research highlights the seasonal compensation effects on the interactions between extreme climate events and the biosphere. Plain Language Summary: Winter storms become more common and frequent in warm areas; however, their impacts have seldom been investigated. It is therefore essential to qualify the impacts of winter storms on ecosystems. In 2021 February, Texas was attacked by several heavy ice storms, which caused widespread economic and ecological influences. This study evaluated the 2021 February Texas ice storm effects on phenology and carbon cycle with satellite‐based measurements. Our results indicate a significant delay in spring leaf area index/gross primary production (GPP) phenology due to the ice storm. Both 2021 spring GPP/NEP was reduced and Texas became the carbon source from the carbon sink in the 2021 spring. However, due to the higher precipitation during April‐August recharged the soil water, which enhanced the vegetation growth and carbon uptake, and offset the spring GPP reduction induced by the February ice storm. Key Points: Texas during 2021 spring became a carbon source, but gross primary production (GPP) was increased across Texas in 2021 2021 February ice storm did not increase the root zone soil moisture, but precipitation during March‐August recharged the water supply Abundant summer soil moisture compensated for the reductions of spring GPP induced by the 2021 ice storm